Settings for Early Childhood Education Teacher Assistance in Gresik Regency - Masturoh, Umi; Noorhayati, Siti Mahmudah; Mufarochah, Siti; Yuliani, Naning (PUDAK: Local Wisdom Community Journal, 2023)
The PAUD teacher mentoring activity program in the Gresik Regency area in each sub-district has its own characteristics and uniqueness, there are 2 - 5 units in each sub-district in Gresik Regency which have almost the same problems as other units, namely in terms of lack of enthusiasm for competitiveness between units. one unit with another, lack of order in administration, as well as PAUD teachers' lack of understanding of the development of Early Childhood learning media. The aim of the PAUD teacher mentoring activities in each sub-district is to; 1) Strengthening and empowering, 2) Carrying out integrated unit promotions, 3) Providing workshops and training in the form of making educational game tools (APE) that are adapted to Curriculum 13 and early Asian education learning models. The target of this PAUD teacher mentoring activity is to manage PAUD units located in each sub-district. This service uses a descriptive method regarding the real picture in the educational unit in the form of delivering material, assignments, questions and answers and discussions, workshops dividing into small groups, training in making educational game tools (APE) with the main focus for Early Childhood (AUD). The expected results are the implementation of the Unit Based Management (MBS) program from empowerment activities, promotion programs integrated with units and increased understanding of teachers regarding the creation of Educational Game Tools (APE) for Early Childhood Children. It is hoped that this PAUD teacher mentoring activity will receive good appreciation from the units in Gresik Regency and all educators and teaching staff as having a strategic meaning related to improving the quality of PAUD in Gresik Regency.